Review: Impact of Helminth Infection on Antimycobacterial Immunity—A Focus on the Macrophage - Lang, Roland; Schick, Judith (Frontiers in Immunology, 2017)
Successful immune control of Mycobacterium tuberculosis (MTB) requires robust CD4+ T cell responses, with IFN as the key cytokine promoting killing of intracellular mycobacteria by macrophages. In contrast, helminth infections typically direct the immune system toward a type 2 response, characterized by high levels of the cytokines IL-4 and IL-10, which can antagonize IFN production and its biological effects. In many countries with high burden of tuberculosis, helminth infections are endemic and have been associated with increased risk to develop tuberculosis or to inhibit vaccination-induced immunity. Mechanistically, regulation of the anti-mycobacterial immune response by helminths has been mostly been attributed to the T cell compartment. Here, we review the current status of the literature on the impact of helminths on vaccine-induced and natural immunity to MTB with a focus on the alterations enforced on the capacity of macrophages to function as sensors of mycobacteria and effector cells to control their replication.